Evaluasi Risiko Postur Kerja Operator Workshop: Studi Kasus CV XYZ di Sleman Yogyakarta - Anirawilda Purba; Her Tafga Arfanindita; Siti Mardiyah; Welly Mahardhika (Tekinfo: Jurnal Ilmiah Teknik Industri dan Informasi, 2025)
Manual material handling (MMH) is a major component of work activities in Indonesia, however it is often performed incorrectly. This can increase the risk of occupational accidents, such as musculoskeletal disorders. According to WHO data, musculoskeletal disorders are the second leading cause of disability worldwide. Based on this issue, this study aims to evaluate working posture and physiological workload risks among workshop operators at CV. XYZ, Sleman, Yogyakarta. It also provides ergonomic-based improvement recommendations. The methods used include Energy Consumption (BMR), Cardiovascular Load (CVL), Nordic Body Map (NBM), and Rapid Entire Body Assessment (REBA). Data were collected through direct observation, interviews, pulse rate measurement, and documentation of working postures from four operators. The results show that the energy consumption was adequate for all workers. Three out of four workers had REBA scores in the high-risk category, and one worker showed fatigue with a %CVL value above 30%. Musculoskeletal complaints, mainly in the back and calves, were consistent with Nordic Body Map results. Adding chairs and worktables reduced REBA scores to the medium risk category at all workstations. The proposed ergonomic design could minimize Musculoskeletal Disorders (MSDs), increasing comfort and productivity. Regular posture and workload evaluations are recommended. Implementing ergonomic work design has proven effective in reducing risks and improving performance.